Emil’ Keme. Le Maya Q’atzij /Our Maya Word: Poetics of Resistance in Guatemala. U of Minnesota P, 2021. - Rigoberto Guevara (Studies in 20th & 21st Century Literature, 2022)
Review of Emil’ Keme. Le Maya Q’atzij /Our Maya Word: Poetics of Resistance in Guatemala. U of Minnesota P, 2021. 248 pp.
Keywords: Maya; Guatemala; resistance; poetry; colonialism; sexuality